Preventívny úcinok zeolitu pri intoxikácii potkanov látkou VX - Mojzis, J; Nistiar, F; Kovác, G; Mojzisová, G (Veterinarni medicina, 1994)
In the present paper the effect of zeolite tuff (61% clinoptilolite) was investigated on cholinesterase activity in brain, liver, spleen, femoral muscle, heart, stomach, duodenum, colon and erythrocytes in sewer-rats after peroral intoxication with VX substance (65.5 micrograms/kg). Fig. 1 shows the ChE activity in the tissues and erythrocytes in the animals of control group and in the group of animals after intoxication with VX substance. The highest activity in the control group was found in brain and duodenum. The enzyme activity in the femoral muscle had the lowest values. A significant decrease in the ChE activity (P < 0.001 or P < 0.01) occurred in all the investigated samples in the group of animals intoxicated with the VX substance. highest enzyme inhibition was observed in erythrocytes (97.9%), stomach (97.9%), brain (95.4%) and liver (94.7%) if compared with the control group. The relatively lowest inhibition was found out in duodenum and colon. In the group administered zeolite before intoxication (1.0 g/kg five minutes before intoxication) the ChE activity was significantly higher in almost all investigated samples than in the group without zeolite (P < 0.001 or P < 0.01)-Fig. 2. The duodenum is an exception, in which the ChE activity in the zeolite group was lower than in the zeolite-free group (P < 0.001), as well as the colon, in which there were no significant differences in the activity between the groups.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Zeolites; krysa rodu Rattus; Animals; zeolity; Poisoning; Organothiophosphorus Compounds; cholinesterasy; zvířata; cholinesterasové inhibitory; Cholinesterase Inhibitors; Cholinesterases; Rats, Wistar; organothiofosforové sloučeniny; Rats; potkani Wistar; otrava